A mini review on recent nanocellulose production from natural fibers and lignocellulosic biomass via acid hydrolysis - Munawar, Rose Farahiyan; Mohd Abid, Mohd Asyadi 'Azam; Kosnan, Muhammad Akmal; Othman, Intan Sharhida; Abd Razak, Jeefferie; Safie, Nur Ezyanie; Alhamoudi, Fahad Hussain (Penerbit Akademia Baru, 2024)
This review examines the recent advancements in the synthesis of nanocellulose using acid hydrolysis techniques and natural fibres. It focuses on the optimisation of reaction conditions, innovative hydrolysis methods, and the integration of environmentally sustainable and economically viable practices. Through the analysis of contemporary literature, this paper highlights the improvements in yield and quality of cellulose nanocrystals (CNCs) derived from various lignocellulosic biomass sources. Key studies demonstrate that precise control of reaction parameters such as acid concentration, temperature, and duration can significantly enhance CNCs yield. Additionally, technological advancements have facilitated more sustainable and cost-effective production processes, suggesting a promising future for applying nanocellulose widely across various industries.